Age changes in Chiapas sheep breed according to sex - Parés-Casanova, P.M. (2017)
A survey was conducted in order to study changes in body measurements in the Chiapas sheep breed. For this purpose 66 males and 79 females of various ages were measured: body weight, chest girth, knee perimeter, cannon perimeter, coronne perimeter, hock perimeter and ear length. The study reflects a regional change according to age, which are not isometrical. Body weight and chest girth are the most discriminative variables, which presented identical age regression trajectories for both sexes (F=1.006, p=0.317). Although body weight in adult male (>12 months, n=56) was greater than those of females (n=64) (U=1320, p=0.014), and no differences appeared for chest girth (U=1720, p=0.704), regression trajectories for both traits appeared similar.